Medicine, Nationalism, and Revolution in Vietnam: the Roots of a Medical Collaboration to 1945 - Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2003)
Keywords: dept.his

Introduction from the Guest Editor: Forays into the Field of Vietnamese Military Technology - Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2003)
Keywords: dept.his

The venomous course of southwestern opium: Qing prohibition in Yunnan, Sichuan, and Guizhou in the early nineteenth century - Bello, David (The Journal of Asian Studies, 2003)
Keywords: dept.his

The german empire on the brink. the daily-telegraph affair and hale-interview of 1908: an account and documentation - Paddock, TRE (German Studies Review, 2003)
Keywords: dept.his

James Monroe: Oberlin's Christian statesman & reformer, 1821-1898. - Davis, Hugh (The Journal of American History, 2003)
Keywords: dept.his; peer-reviewed

Book Review: Arabia and the Arabs: From the Bronze Age to the Coming of Islam , by Robert G. Hoyland. 324 pages, bibliography, index. New York: Routledge, 2001. 23.95 (Paper) ISBN 0-415-19535-7 - Judd, Steven (Middle East Studies Association Bulletin, 2003)
Keywords: book.review; dept.his

The historiography of american violence - Leonard, Ira M; Leonard, Christopher C (Homicide Studies, 2003)
Historians have generally agreed that the United States has always been an extremely violent nation; however, since the 1950s they have been myopic in their treatment of violence in America and have not provided the American people with essential information about their society and culture. Those historians who focused on violence in America, until the 1990s, have focused on only one form of violence—collective social violence. Largely overlooked, and equally significant, are interpersonal violence (including criminal and domestic violence) and the effect of war. This deficiency helps explain why Americans seem genuinely at a loss to understand the nature, character, and frequency of violence in America's past and present, especially when a high-profile violent incident occurs. This article surveys the historiography of violence in America through the 1990s and examines the contributions of historians and legal scholars who have focused on interpersonal and criminal violence. © 2003, SAGE Publications. All rights reserved.
Keywords: dept.his; historiography; lynching; riots; vigilantism

Book Review: Inventing the schlieffen plan: German war planning 1871–1914: Zuber, Terence: Oxford: Oxford University Press 340 pp., publication date: January 2003 - Paddock, Troy (History: Reviews of New Books, 2003)
Keywords: book review; book.review; dept.his